Ratio Analysis on Tiktok (Social Media) for Qualitative Research Using Explorative Methods - I Putu Hendika Permana; Ni Putu Suci Meinarni (Universitas Warmadewa, 2021)
Information and communication technology is considered important by users, one of its goals is to seek information and communicate remotely through social media. Social media aims to provide convenience in terms of communicating so that it has an impact on users, either it positive or negative perceptions. Currently, Tiktok social media become most popular application. This research was conducted to find the ratios that will be used to systematically show the performance of the Tiktok account. This study uses an exploratory method to find the variables contained in the Tiktok account. These variables will be compared so as to find the relevant ratios to show the performance of a Tiktok account. The results of this study is that the tiktok account has 7 variables and find then 17 ratios that can be used to assess, measure and compare the credibility of a Tiktok account.